Best of Both Worlds: Synergistically Derived Material Properties via Additive Manufacturing of Nanocomposites (Adv. Funct. Mater. 46/2021). (10th November 2021) - Carrola, Mia; Asadi, Amir; Zhang, Han; Papageorgiou, Dimitrios G.; Bilotti, Emiliano; Koerner, Hilmar
Abstract : Additive Manufacturing In article number 2103334, Hilmar Koerner and co‐workers discuss how, with the growth in additive manufacturing, such as 3D printing, nanocomposites have experienced a resurgence due to novel emergent material properties, which are enabled by digitally dialing in morphology over several length scales. Topology optimization of 3D printed nanocomposites takes this to another level with unprecedented control over morphology and material response in structural and electro‐optical applications.